Evaluation of the combined effect of thymol, carvacrol and (E)-cinnamaldehyde on Amblyomma sculptum (Acari: Ixodidae) and Dermacentor nitens (Acari: Ixodidae) larvae - Lopes Novato, Tatiane Pinheiro; Araujo, Laryssa Xavier; Oliveira de Monteiro, Caio Marcio; Maturano, Ralph; Souza Senra, Tatiane de Oliveira; Matos, Renata da Silva [UNESP]; Gomes, Geovany Amorim; Carvalho, Mario Geraldo de; Daemon, Erik (Elsevier B.V., 2015)
This study aimed at assessing the combined effect of thymol, carvacrol and (E)-cinnamaldehyde on Amblyomma sculptum and Dermacentor nitens larvae. The effects resulting from treatments were evaluated by means of the modified larval packet test. In order to determine the LC50, components of essential oils, the monoterpenes thymol, carvacrol and phenylpropanoid (E)-cinnamaldehyde were individually tested at different concentrations. After determining the LC50, each essential oil component was separately evaluated and then combined with another substance at a 1:1 proportion at the LC50 concentration and at 1/2 and 1/4 of the LC50. For A. sculptum, the lowest LC50 value was obtained for (E)-cinnamaldehyde (1.40 mg/ml), followed by thymol (2.04 mg/ml) and carvacrol (3.49 mg/ml). The same order of effectiveness was observed for D. nitens, with values of 1.68, 2.17 and 3.33 mg/ml, respectively. In the evaluation of component associations of essential oils against A. sculptum larvae, only the combinations between carvacrol and thymol (LC50) and carvacrol and (E)-cinnamaldehyde (1/4 LC50) presented a moderate synergetic effect. In turn, for D. nitens larvae, the combinations between thymol and carvacrol (LC50 and 1/2 LC50) presented a synergetic effect, while the others presented an additive or antagonistic effect. Therefore, it can be concluded that the combination of thymol and carvacrol (LC50) has a moderate synergetic effect against A. sculptum larvae, while thymol, combined with carvacrol (LC50 and 1/2 LC50), has a synergetic effect against D. nitens larvae. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Tick; Monoterpene; Phenylpropanoid; Synergism